Construção de Linguagens Específicas de Domínio e a sua Integração com IDEs - Marques, Luís Miguel Godinho Pinho Oliveira (2022)
Low-code platforms are presented as model-based software development solutions. In this sense, they could be described as applications of the Model-driven Engineering (MDE) paradigm. Despite the apparent success of these development platforms, they do not appear to adhere to standards and are frequently closed-source solutions. These characteristics may cause problems in the maintenance and evolution of solutions developed on these platforms in the future. One of these issues is the difficulty in migrating solutions to other platforms, implying that the client/user is dependent on the platform. The goal of the study is to externalize low-code platform modeling or any DSL to more general-purpose integrated development environments (IDE) like Visual Studio Code or Eclipse. As a result, users are able to use DSLs to model their applications in the IDE and integrate them with more general-purpose programming languages. This dissertation starts by providing an overview of the current state of the use of domainspecific language in general-purpose IDE environments. Furthermore, several designs were developed to find the best solution that achieves the goal. The designs are then compared, and the best one is selected to be implemented. The solution developed still has quite some future work to be done. It lacks many of the features found in a full-fledged IDE for a general-purpose language, like Visual Studio Code supports Javascript. Nonetheless, it may be quite useful when deploying a DSL to a generalpurpose IDE.